Prevalence and associated factors for cesarean section among women at a tertiary care hospital in Nepal - Adhikari, Sunaina; Lama, Monika (Journal of Karnali Academy of Health Sciences, 2024)
Background: There has been a global rise in caesarean section (CS) rates for delivery of baby, which is often associated with short and long-term risks. The main objective of this study was to find out the prevalence of and associated factors for CS delivery against vaginal delivery at a tertiary care hospital of Biratnagar, Nepal. Methods: A cross-sectional study was carried out in October 2022 using consecutive sampling to include 178 women who gave birth during the study period. Data on socioeconomic and obstetric variables were collected through face-to-face interviews and hospital records. Descriptive and chi-square analysis were performed to identify the factors associated with CS. Results: The mean age of women was 24.64 (± 4.64) years. The prevalence of CS was 38.2%. Half of the women were primigravida at the time of presentation. Common reasons for CS were previous history of CS (23.45%) and fetal distress (20.98%). Women under 25 years had higher odds of CS compared to those aged 25 years or older (OR = 2.007, 95% CI [1.017-3.961]). Likewise, women who had previous CS (OR = 6.721, 95% CI [2.526 – 17.884]) and fetal distress (OR = 3.157, 95% CI [2.516-3.961]) were more likely to have CS. Conclusions: Caesarean births accounted for more than one third of all births. Age, order of gestation (parity), previous CS and fetal distress were significantly associated with higher CS rates.